PERTANGGUNGJAWABAN PIDANA DALAM TINDAK PIDANA MILITER ( Studi Tindak Pidana Militer Di Kosek Hanudnas III Medan) - Muhammad Hykna Kurniawan Lubis; Syafruddin Kalo; Mahmud Mulyadi; Muhammad Hamdan (Universitas Sumatera Utara, 2017)
ABSTRACT Indonesian National Army consists of the Indonesian Army, Indonesian Navy, Indonesian Air Force. In carrying out the responsibilities of course there is the possibility of irregularities committed by members of the Indonesian National Army. Deviations that one of them is a military offense. Every crime committed by members of the Indonesian National Army settled in military courts. The results showed that the request of criminal liability against members of the military who commit the crime of military experience various obstacles, such as procedural obstacles and barriers that come from matter legislation relating to the setting military offense itself. All entities to improve the effectiveness of supervision attached or internal control as a function of command, carry out program personnel development and mental development to improve compliance, obedience and discipline of soldiers against the rule of law, then an evaluation factor contributing to the cause so it can be used as an ingredient in prevention and penaggulangan, and the latter are cracked down any military personnel involved in criminal acts. Besides, it is also the need to revise Law No. 31 Year 1997 on Military Justice, in particular to Article 124 paragraph (4), Article 141, paragraph (10), and Article 143, because these Articles is a matter of law that are multiple interpretations. Keywords: criminal liability, the military, a criminal offense.